Analisis Kerusakan Retract Actuator Nose Landing Gear Pada Pesawat Boeing 737-800 Next Generation - Pambekti, Arif; Misi Okia, Yudha; Kurniawan, Riski; Al Huda, Luqman; Evan, Bah; Kamal Fajri, Amrisal; Tri Efendi, Erwan (BULLET : Jurnal Multidisiplin Ilmu, 2024)
The retract actuator is one of the main parts of the landing gear, which functions to retract or extend. The retract actuator must be free in its operation and its movement must also be smooth. If the aircraft experiences a failure of the retract actuator function, namely the retract actuator in a slow to retract condition. Where there is a slowdown during retract and extend. Careful handling is required and in accordance with applicable aircraft maintenance procedures, especially regarding slow to retract conditions. This study uses a direct observation method for the analysis of the troubleshooting process on the B737-800 NG in the Merpati Maintenance Facility hangar. In addition, this study also uses the Fault Tree Analysis method to obtain the cause of the failure of the standby reservoir. After analyzing the results, the possible causes of failure in the Retract Actuator are by using the Fault Tree Analysis (FTA) method, the minimum cut set results are obtained with calculations consisting of 18 basic events.